Evaluation of Thyroid Uptake of 99mTc Pertechnetate Using Gamma Camera and Dose Calibrator Methods in the Sudanese Population - Zobai Tageldin Yousif; Ikhlas A. Mohamed; Salah Ali Fadlalla; Salem Saeed Alghamdi; Lubna Bushara; Mustafa Z. Mahmoud; Mohamed Yousef; Hamid Osman; Hanady Elyas Osman (International Journal of Biomedicine, 2022)
Background: Estimation of the thyroid gland volume is generally considered important in several pathologic situations. The main objective of this study was to evaluate the thyroid uptake (TU) of 99mTcO4- in Sudanese people, using gamma camera and dose calibrator methods and comparing the results with international TU levels. Methods and Results: The study was conducted in 2020 at the National Cancer Institute (Wad Madani state, University of Gezira, Sudan). This study included 64 patients (58 females and 6 males) aged 13-81 years (37.25±14.58 years) with normal TU. Most patients (43.8%) were in the age subgroup of 31-48 years, followed by 39.1% in the age subgroup of 13-30 years.Two calibration methods were used to calculate full and empty syringes before and after radiopharmaceutical injection: a) using a dose calibrator measuring in MBq; b) with gamma camera images of the full and empty syringes for 1 minute (counts). In the dose calibrator, the activity and time of a 99mTc point source in a syringe were monitored, the point source was precisely aligned with the center of the camera, and a static image was obtained with static parameters at a distance of 5cm and 7cm between source and pinhole collimator (265×265 matrix). The study showed that the TU values using the dose calibrator method were more consistent with radiation protection principles of minimizing the exposure to radiation for staff. The method also had higher values than those measured with a gamma camera due to the scatter radiation. The relationship between TU of 99mTcO4- with syringe measured by dose calibrator and gamma camera at a distance of 5cm and 7cm, given a coefficient of determination (R2) of 0.9937 and 0.9591, respectively Conclusion: There was no big change in the TU between the two methods, especially at 5cm object-to-pinhole distance, where it gave the best result for optimum imaging in the 99mTcO4- TU test.